Structure and mechanism of action of the hydroxy aryl aldehyde class of IRE1 endoribonuclease inhibitors - Sanches, Mario (Nat Commun, 2014)
Endoplasmic reticulum (ER) stress activates the unfolded protein response and its dysfunction is linked to multiple diseases. The stress transducer IRE1α is a transmembrane kinase endoribonuclease (RNase) that cleaves mRNA substrates to re-establish ER homeostasis. Aromatic ring systems containing hydroxy-aldehyde moieties, termed hydroxy aryl aldehydes (HAA), selectively inhibit IRE1α RNase and thus represent a novel chemical series for therapeutic development. We solved crystal structures of murine IRE1α in complex with three HAA inhibitors. HAA inhibitors engage a shallow pocket at the RNase active site through pi-stacking interactions with His910 and Phe889, an essential Schiff base with Lys907 and a H-bond with Tyr892. Structure activity studies and mutational analysis of contact residues define the optimal chemical space of inhibitors and validate the inhibitor binding site. These studies lay the foundation for understanding both the biochemical and cellular functions of IRE1α using small molecule inhibitors and suggest new avenues for inhibitor design.